Design and synthesis of a multivalent catch-and-release assay to measure circulating FXIa. Issue 200 (April 2021) - van der Beelen, S.H.E.; Agten, S.M.; Suylen, D.P.L.; Wichapong, K.; Hrdinova, J.; Mees, B.M.E.; Spronk, H.M.H.; Hackeng, T.M.
Abstract: Background: Decreased blood coagulation factor (F)XIa levels have been shown to protect from thrombosis without bleeding side effects, but less is known on effects of increased FXIa levels. Studies are hampered by lack of a reliable and robust method for FXIa quantification in blood. We aim to develop a new assay employing a unique multivalent catch-and-release system. The system selectively isolates and protects homodimeric FXIa from plasma and releases free FXIa allowing subsequent quantification. Methods: A dynamic multivalent construct was synthesized by complexing four identical FXIa inhibitors from the snake Bungarus Fasxiatus to avidin through desthiobiotin-PEG-linkers, allowing dissociation of FXIa by excess biotin. PEG-linker lengths were optimised for FXIa inhibitory activity and analysed by Michaelis-Menten kinetics. Finally, the catch-and-release assay was validated in buffer and plasma model systems. Results: Monovalent and multivalent inhibitor constructs were successfully obtained by total chemical synthesis. Multimerisation of Fasxiator resulted in a 30-fold increase in affinity for FXIa from 1.6 nM to 0.05 nM. With use of this system, FXIa could be quantified down to a concentration of 7 pM in buffer and 20 pM in plasma. Conclusion: In this proof-of-concept study, we have shown that the catch-and-release approach is a promising technique to quantify FXIa in plasma or buffer. By binding FXIa to the multivalent construct directly after blood drawing, FXIa is hypothesized to be inaccessible for serpin inhibition or auto inactivation. This results in a close reflection of actual circulating FXIa levels at the moment of blood drawing. Highlights: Circulating FXIa can be quantified by capturing it from plasma. A multivalent catch-and-release assay based on venom-derived Fasxiator was employed. Quantification of FXIa in buffer or plasma down to 7 and 20 pM, respectively.